Analysis of Reasoning Ability Assess from Learning Independence and Learning Interest - Suci Hidayati (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The purpose of this study was to determine the analysis of mathematical reasoning abilities in terms of learning independence and interest in learning in class VIII students of SMP N 2 Banyubiru in the 2019/2020 academic year. This research is a qualitative research with a descriptive approach. Data collection was carried out using several methods, including questionnaires, tests, interviews, and documentation. Data analysis was performed by first focusing on important data. Then it is presented in a descriptive-analytic text, and conclusions are drawn by describing it descriptively. The results of this study indicate that: The mathematical reasoning abilities of students with a high level of learning independence and a high interest in learning indicate that they have been able to meet the four mathematical reasoning indicators totaling 2 students. The mathematical reasoning abilities of students with a level of learning independence and moderate interest in learning indicate that they are able to meet the indicators of mathematical reasoning, but there is one indicator that is not fulfilled, amounting to 5 students. Students' mathematical reasoning abilities with a low level of learning independence and interest in learning were unable to meet the mathematical reasoning indicators, amounting to 3 students. Factors that affect mathematical reasoning abilities in terms of learning independence and interest in learning are the level of intelligence, interest and willingness in learning mathematics as well as environmental conditions around students which are still less supportive of students' thinking abilities and thinking abilities.